Effects of airway tree asymmetry on the emergence and spatial persistence of ventilation defects - Leary, D. (American Physiological Society, 2014)
Asymmetry and heterogeneity in the branching of the human bronchial tree are well documented, but their effects on bronchoconstriction and ventilation distribution in asthma are unclear. In a series of seminal studies, Venegas et al. have shown that bronchoconstriction may lead to self-organized patterns of patchy ventilation in a computational model that could explain areas of poor ventilation [ventilation defects (VDefs)] observed in positron emission tomography images during induced bronchoconstriction. To investigate effects of anatomic asymmetry on the emergence of VDefs we used the symmetric tree computational model that Venegas and Winkler developed using different trees, including an anatomic human airway tree provided by M. Tawhai (University of Auckland), a symmetric tree, and three trees with intermediate asymmetry (Venegas JG, Winkler T, Musch G, Vidal Melo MF, Layfield D, Tgavalekos N, Fischman AJ, Callahan RJ, Bellani G, Harris RS. Nature 434: 777–782, 2005 and Winkler T, Venegas JG. J Appl Physiol 103: 655–663, 2007). Ventilation patterns, lung resistance (R(L)), lung elastance (E(L)), and the entropy of the ventilation distribution were compared at different levels of airway smooth muscle activation. We found VDefs emerging in both symmetric and asymmetric trees, but VDef locations were largely persistent in asymmetric trees, and bronchoconstriction reached steady state sooner than in a symmetric tree. Interestingly, bronchoconstriction in the asymmetric tree resulted in lower R(L) (∼%50) and greater E(L) (∼%25). We found that VDefs were universally caused by airway instability, but asymmetry in airway branching led to local triggers for the self-organized patchiness in ventilation and resulted in persistent locations of VDefs. These findings help to explain the emergence and the persistence in location of VDefs found in imaging studies.